On Cycles Through Vertices of Large Semidegree in Digraphs - Darbinyan, Samvel Kh.; Karapetyan, Iskandar A. (Mathematical Problems of Computer Science, 2021)
Let D be a strong digraph on n = 2m+1 ≥ 5 vertices. In this paper we show that if D contains a cycle of length n—1, then D has also a cycle which contains all vertices with in-degree and out-degree at least m (unless some extremal cases).